1997
DOI: 10.1097/00004714-199710000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Paroxetine Increases Heart Rate Variability in Panic Disorder

Abstract: Panic patients have decreased heart rate variability, a risk factor for sudden cardiac death, and increased rates of cardiac death and stroke. Imipramine has been found to further reduce heart rate variability in panic. This study uses power spectral analysis to compare autonomic components of heart rate variability in 16 unmedicated control subjects and 17 panic patients before and after treatment with paroxetine at 20 mg/day for 4 weeks. Patients had higher predrug reclining and standing sympathetic activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Concerning psychotropic treatments, two studies have investigated the impact of pharmacological intervention in isolation on HRV in anxiety patients. First, Tucker et al (110) examined the effect of paroxetine (an SSRI) administration on HRV in 17 PD patients. After 4 weeks of 20 mg of paroxetine daily, parasympathetic activity was significantly increased in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning psychotropic treatments, two studies have investigated the impact of pharmacological intervention in isolation on HRV in anxiety patients. First, Tucker et al (110) examined the effect of paroxetine (an SSRI) administration on HRV in 17 PD patients. After 4 weeks of 20 mg of paroxetine daily, parasympathetic activity was significantly increased in patients.…”
Section: Discussionmentioning
confidence: 99%
“…In depression, in contrast to other antidepressant categories (e.g., tricyclic antidepressants, serotonin-norepinephrine reuptake inhibitors; Siepmann et al, 2007 ; Kemp et al, 2010 ; Chang et al, 2012 ), SSRI treatment has been reported not to have a significant impact on resting HRV ( Rechlin, 1994 ; Straneva-Meuse et al, 2004 ; Koschke et al, 2009 ; Kemp et al, 2010 , 2011 , 2014 ; Brunoni et al, 2013 ; Hanson et al, 2013 ), although contradictory results have also been reported ( Licht et al, 2010 ). In patients with panic disorder or post-traumatic stress disorder, SSRI treatment has been mainly associated with positive effects on HRV measures, i.e., reduced sympathetic activity/normalized ANS activity and baroreflex response ( Tucker et al, 1997 ; Cohen et al, 2000 ). SSRI treatment in patients with cardiovascular diseases has been also associated with an improvement of HRV indices independent of the improvement of depressive symptoms, suggesting a clear benefit for the prognosis of the cardiovascular disease ( Gorman and Sloan, 2000 ; Leftheriotis et al, 2010 ; Mazza et al, 2010 ; Pizzi et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, effects of SSRI treatment on autonomic reactivity have been only sparsely investigated, predominantly in psychiatric patients using various stressor models. Effects of SSRI treatment on autonomic reactivity have been reported in patients with panic disorder and post-traumatic stress disorder, suggesting a positive effect of SSRIs on HRV reactivity to physiological (orthostatic) or psychological challenges, towards normalizing autonomic indices ( Tucker et al, 1997 , 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Paroxetine can improve heart rate variability and induce a decrease in the relative cardiac sympathetic activity occurring in patients with PD 102 105 . In addition, SSRIs have some beneficial effects on the cardiovascular system, such as inhibiting platelet aggregation, collagen, and thrombin, exerting anti-inflammatory effects, and improving endothelial function 106 , which may be protective against cardiovascular morbidity in patients with PD.…”
Section: Are Successful Treatments Of Panic Disorder Specifically Actmentioning
confidence: 99%